Fabrication and corrosion resistance of a hydrophobic micro-arc oxidation coating on AZ31 Mg alloy. (January 2015) - Cui, Xue-jun; Lin, Xiu-zhou; Liu, Chun-hai; Yang, Rui-song; Zheng, Xing-wen; Gong, Min
Highlights: A green and effective approach to inhibiting corrosion of Mg alloys was proposed. Stearic acid was first used to modify surface of micro-arc oxidation (MAO) coating. A hydrophobic MAO coating was fabricated on AZ31 Mg alloy. Formation mechanism of a hydrophobic MAO coating was proposed. The hydrophobic MAO coating exhibits better corrosion resistance. Abstract: A hydrophobic surface was fabricated through the micro-arc oxidation (MAO) and subsequent stearic acid surface modification of AZ31 Mg alloy, achieving a maximum water contact angle of 151.5° after 10 h of modification. Through surface analyses and investigation into the corrosion behavior, this hydrophobicity is ascribed to a combination of the MAO coating's rough micro-pore structure and the formation of a stearic acid monolayer through bidentate bonding. The hydrophobic MAO coating effectively inhibits corrosion of the Mg alloy, especially pitting corrosion, and demonstrates that surface modification could further increase or accelerate the application of MAO treatment to Mg alloys.